Pendayagunaan Zakat Untuk Penanggulangan Pandemi Covid-19 Perpektif Filsafat Hukum Islam - Irfandi EZ; Nurul Maisyal (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2020)
The global pandemic Covid-19 that occurred in Indonesia made people experience a difficult situation that requires assistance in terms of support, material and financial. Zakat as a source of social funds in Islam has a strategic role to meet these needs. This study examines the importance of zakat for tackling the Covid-19 pandemic. This research is a library research and data collection technique carried out through library studies, using Islamic legal philosophy approach, and results in the conclusion that zakat may be given to Covid-19 affected parties, both for medical teams, corona patients and one of citizens who family has confirmed positive corona, people affected by PHK due to phsycal or social distancing implemented by the government to minimize the transmission of Covid-19, etc